2018
DOI: 10.1074/jbc.ra118.001934
|View full text |Cite
|
Sign up to set email alerts
|

The mucinous domain of pancreatic carboxyl-ester lipase (CEL) contains core 1/core 2 O-glycans that can be modified by ABO blood group determinants

Abstract: Carboxyl-ester lipase (CEL) is a pancreatic fat-digesting enzyme associated with human disease. Rare mutations in the CEL gene cause a syndrome of pancreatic exocrine and endocrine dysfunction denoted MODY8, whereas a recombined CEL allele increases the risk for chronic pancreatitis. Moreover, CEL has been linked to pancreatic ductal adenocarcinoma (PDAC) through a postulated oncofetal CEL variant termed feto-acinar pancreatic protein (FAPP). The monoclonal antibody mAb16D10 was previously reported to detect a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 64 publications
1
19
0
Order By: Relevance
“…Using this model, we found that CEL-HYB and CEL-MODY affected the intracellular fate of a FLAG-tagged CEL-WT protein (Figures 6 and 7), as the latter was found to be more intracellularly accumulated when coexpressed with a pathogenic CEL variant than with CEL-WT-V5. Intriguingly, the rate of CEL secretion has been suggested to positively correlate with the cells' capability to O-glycosylate the CEL VNTR region [9], partially explaining the impaired secretion of CEL-HYB and CEL-MODY, as the VNTR regions of these enzymes are shorter and potentially less O-glycosylated compared to CEL-WT [19,23,27]. However, it does not explain how the pathogenic CEL variants affect the intracellular fate of CEL-WT.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Using this model, we found that CEL-HYB and CEL-MODY affected the intracellular fate of a FLAG-tagged CEL-WT protein (Figures 6 and 7), as the latter was found to be more intracellularly accumulated when coexpressed with a pathogenic CEL variant than with CEL-WT-V5. Intriguingly, the rate of CEL secretion has been suggested to positively correlate with the cells' capability to O-glycosylate the CEL VNTR region [9], partially explaining the impaired secretion of CEL-HYB and CEL-MODY, as the VNTR regions of these enzymes are shorter and potentially less O-glycosylated compared to CEL-WT [19,23,27]. However, it does not explain how the pathogenic CEL variants affect the intracellular fate of CEL-WT.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, it was important to investigate CEL in acinar cells such as the murine 266-6 cell line, as these cells provide the transfected and endogenously expressed CEL proteins with a proper exo-and endocytic machinery. The human pancreatic ductal cell line PANC-1 does not express CEL [27]. However, being a cancer cell line, these cells might exhibit properties other than normal ductal cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations